2020
DOI: 10.1038/s41598-020-58568-5
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Medial Calcification through Enhanced small Extracellular Vesicle Release in Smooth Muscle-Specific Asah1 Gene Knockout Mice

Abstract: Arterial medial calcification (AMC) involves an increased small extracellular vesicle (sEV) secretion and apatite calcium precipitation in the arterial wall. The mechanisms mediating AMC remain poorly understood. In the present study, smooth muscle-specific acid ceramidase (Ac) gene knockout mice (Asah1 fl/fl /SM cre) were used to demonstrate the role of lysosomal ceramide signaling pathway in AMC. Asah1 fl/fl /SM cre mice were found to have more severe AMC in both aorta and coronary arteries compared to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 88 publications
(114 reference statements)
0
35
0
Order By: Relevance
“…Our findings in podocytes demonstrated that inhibition or activation of the TRPML1 channel modulates the interaction of lysosomes and MVBs, thereby regulating the exosome release from these cells [31]. Also, recently, we found that inhibition of TRPML1 channel activation in coronary arterial SMCs due to deficiency of acid ceramidase may lead to the reduction of lysosome-MVB interaction and consequent prolongation of MVB fate, increasing SMC-derived small extracellular vesicle (sEV) release initiating arterial medial calcification (AMC) [55]. Based on these findings, we hypothesized and found that Mcoln1 −/− mice exhibited abnormal lysosome positioning and increased sEV levels in the arterial medial SMCs, which may contribute to the arterial stiffness during the development of AMC.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our findings in podocytes demonstrated that inhibition or activation of the TRPML1 channel modulates the interaction of lysosomes and MVBs, thereby regulating the exosome release from these cells [31]. Also, recently, we found that inhibition of TRPML1 channel activation in coronary arterial SMCs due to deficiency of acid ceramidase may lead to the reduction of lysosome-MVB interaction and consequent prolongation of MVB fate, increasing SMC-derived small extracellular vesicle (sEV) release initiating arterial medial calcification (AMC) [55]. Based on these findings, we hypothesized and found that Mcoln1 −/− mice exhibited abnormal lysosome positioning and increased sEV levels in the arterial medial SMCs, which may contribute to the arterial stiffness during the development of AMC.…”
Section: Discussionmentioning
confidence: 80%
“…Isolation of mouse CASMCs was described previously [34]. Briefly, CASMCs were cultured in Dulbecco's modified Eagle's medium (DMEM, Gibco Gaithersburg, MD, USA), supplemented with 10% fetal bovine serum (Gibco) and 1% penicillin-streptomycin (Gibco Gaithersburg, MD, USA) in humidified 100% air and 5% CO2 mixture at 37 • C. Confluent cells (70%-80%) were treated with or without high phosphate (Pi) (3 mmol/L) [35] and then incubated with TRMPL1 channel agonist, MLSA-1 (10 µM, Sigma-Aldrich Chemicals, St. Louis, MO, USA) and TRMPL1 channel blocker, verapamil (10 µM, Cayman Chemical, Ann Arbor, MI, USA) incubated for 24 h [31,55] . The average body weight for the male mice aged 12-14 weeks ranged from~25-30 g. All mice were grossly normal; the homozygous (Mcoln1 −/− ) mice, however, were prone to developing hind-limb paralysis by the age of 28 weeks, and the average life expectancy was 8 months.…”
Section: Primary Culture Of Mouse Casmcsmentioning
confidence: 99%
“…In short, if TPC2 plays a role in acute HPV it is a subtle one. Alternatively, there may be redundancy of function within the system, perhaps through the expression of alternative lysosome-resident, calcium permeable channels such as TRPML1 [ 129 , 130 , 131 , 132 ] and TRPM2 [ 133 , 134 ], each of which has been proposed to couple to RyRs and impact smooth muscle function and vascular reactivity. In this respect it is notable that mTORC1-dependent modulation of autophagy impacts pulmonary vascular remodeling [ 127 , 128 ], given that inhibition of mTORC1 [ 135 ] may regulate lysosomal TPC2 [ 121 ] and TRPML1 [ 136 ].…”
Section: Location Location: Dispense With the Wax And Shine Some mentioning
confidence: 99%
“…Endolysosome targeted TRPML1 [ 129 , 130 , 131 , 132 ] and TRPM2 [ 133 , 134 ] by mTORC1 and/or ADP-ribose;…”
Section: We Will Be Fine Its Nano Time: Even Though “Nasca” Say mentioning
confidence: 99%
“…Indeed, lysosome dysfunction or injury by various lysosomotropic agents such as bafilomycin A and chloroquine are reported to increase the exosome release. Recently, we demonstrated that inhibition of lysosomal AC causes the lysosome trafficking dysfunction leading to impaired fusion of lysosomes with MVBs Yuan et al, 2019b;Bhat et al, 2020). AC inhibition blocks the lysosomal TRPML1-Ca 2+ channel activity and disturbs lysosome-MVB interaction resulting in increased exosome release in podocytes and VSMC Bhat et al, 2020).…”
Section: Discussionmentioning
confidence: 99%